Geochemistry of Volcanic Rocks in Ponelo Island, North Gorontalo, Indonesia - Nurahmah, Siti Chusnul Chatimah; Rosana, Mega Fatimah; Haryanto, Iyan (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Ponelo Island is located in the northern part of Sulawesi, which is still an enigma regarding the genesis of the volcanic rocks found on this island. Therefore, the objective of this study is to understand the petrogenesis and tectonic implication of these volcanic rocks. Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) to obtain trace and rare earth elements is the method of this study. The volcanic rocks found on Ponelo Island consist of basalt and basaltic andesite rocks with a calc-alkaline affinity. The transition data suggested a highly fractionated cause of low transition element (Ni=17-38 ppm; Cr=13-47) compared to primary magma concentration, anomalies negative of Ba, Sr, and Ti of spider diagrams, and negative anomaly of Eu (Eu/Eu*=0.88-0.99). Relationship between low concentration between Ce/Y (0.74-0.76) and La/Yb vs Sm/Yb ratio indicated ~5% spinel-lherzolite mantle source partial melting. On the other hand, incompatible element ratios, such as Ba/Nb (39.03-45.28), Ba/Th (75.52-82.67), Rb/Nb (3.93-6.22), K/Nb (1772.22-2703.45), Ba/La=13.67-14.57, Th/La (0.17-0.18), La/Nb (2.91-3.16), depleted Nb/U (6-6.74), and also lack of xenolith or enclaves indicate cryptic crustal contamination.  The slab-derived fluid indicated by ratios of Rb/Y (0/019-0/05), Nb/Y (0.10-0.11), Th/Yb (0.52-0.61), and Ba/La ratio (13.29-14.57). Ponelo volcanic rocks shows typical calc-alkaline island arc tectonic setting particularly with enrichment in ion lithophile element (LILE) and light rare earth elements (LREE) along with depletion in high field strenght elements (HFSE) and heavy rare earth elemets (HREE), as shown by spider diagrams.